Techniki chirurgiczne stosowane przy przeszczepach rąbkowych komórek macierzystych - Wylęgała, Edward; Tarnawska, Dorota; Orzechowska-Wylęgała, Bogusława (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
Limbal stem cells (LSC) deficiency is one among the causes of corneal transparency loss. The only effective management is LSC transplantation. In available techniques the source of donor tissue containing LSC can be healthy fellow eye (CLAU, EVELAU), living-related (lr-CLAL, lr-EVELAL) or cadaveric donor (c-CLAL). From among them, the most efficient and the safest procedure is transplantation of cultured stem cells. Preoperative diagnosis and ocular surface condition determine the choice, of which procedure is the best. The surgical restoration of ocular surface is the sequence of procedures and the penetrating keratoplasty is the ultimate rehabilitative step in this process.